Penerapan Pembelajaran Tanggap Budaya (Culturally Responsive Teaching) pada Pembelajaran Bahasa Indonesia untuk Materi Teks Puisi Kelas VIII di SMP Negeri 2 Indramayu - Adian Saputra; Embang Logita; Nana TWinata; Rochman Rochman (Fakultas Pendidikan IAI Pangeran Dharma Indramayu, 2025)
This study aims to describe the application of Culturally Responsive Teaching in Indonesian Language learning for grade VIII Poetry Text Material. The research method used is descriptive qualitative. Data collection was carried out using instruments in the form of interviews, observation sheets, and documentation. The results of the study indicate that the application of Culturally Responsive Learning in poetry learning in grade VIII has a positive impact on student involvement and understanding, this can be seen from the responses of students, 93.5% of students agree that the application of culturally responsive learning in poetry material makes students more active in learning because it is associated with the culture of students.